2019
DOI: 10.26803/ijlter.18.13.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Students’ Experiences of Self-Regulated Learning during a Large Flipped Classroom Course in Teacher Education

Abstract: The aim of the study was to explore teacher students' experiences of self-regulated learning and the teaching-learning environment during a course following the Flipped Classroom approach. Theoretical perspectives include self-regulated learning and motivation, especially in terms of the fore-thought phase in which the students set goals for their studying and learning processes, and monitoring. Goals are approached, in addition to the immediate study context, from more general perspectives of teacher educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore Hirsto, Väisänen, and Arffman (2019) added under theoretical perspectives in flipped classroom, selfregulated learning and motivation, especially in terms of the fore-thought phase in which the students set goals for their studying and learning processes, and monitoring are also one of the important parts in flipped learning. The learning should focus on not only achieving goals for the students but also teachers' perspectives and preferences as well (Hirsto et al, 2019).…”
Section: Flipped Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore Hirsto, Väisänen, and Arffman (2019) added under theoretical perspectives in flipped classroom, selfregulated learning and motivation, especially in terms of the fore-thought phase in which the students set goals for their studying and learning processes, and monitoring are also one of the important parts in flipped learning. The learning should focus on not only achieving goals for the students but also teachers' perspectives and preferences as well (Hirsto et al, 2019).…”
Section: Flipped Learningmentioning
confidence: 99%
“…It may also due to lack or less of practical studies; the Malaysian teachers were not assured to use the flipped approach in lower primary school (Lie & Yunus, 2019). Students also need to change their habit or usual way of doing things in the new learning environment by studying the given contents before class which seems rather challenging for younger students (Hirsto et al, 2019). Nonetheless, there has yet any study conducted especially for lower primary students in rural area in this country after the implementation of CEFR that based on the perception and attitude in flipped approach towards grammar learning.…”
Section: Previous Studies On Students' Perception In Learning Grammar Using Flipped Classroommentioning
confidence: 99%
“…Unfortunately, MOOCs suffer from a high drop-out and low success rates. Furthermore, prior research has shown that students often do not possess the self-regulated learning skills necessary to succeed in flipped classrooms (a form of blended learning) [14]. Both MOOC and flipped classroom scenarios could therefore benefit from models being able to predict student success accurately and in an interpretable way.…”
Section: Learning Contextmentioning
confidence: 99%
“…flipped learning (cf. Hirsto et al, 2019). Moreover, if the basis of a skill were observed beforehand via 360 video, the time in the classroom or workshop could be efficiently used for hands-on practice with teacher supervision.…”
Section: Social Interaction In Skill Learning and 360 Vlementioning
confidence: 99%